2020
DOI: 10.1007/s41403-020-00101-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Design of PPE Based on Electrostatic Principle to Eliminate Viruses (SARS-CoV-2)

Abstract: The ongoing global pandemic due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is in the crucial stage. The vaccine is still at the developing stage. Currently, the only way to check the spreading of this virus is self-isolation. It is reported that a good number of health workers are infected while treating patients suffering from COVID 19. Therefore, an effort is made to develop a system that can enhance safety and check unwanted viruses. Although the complete specification of the SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Sanitization based research is a void where technologies and research other than those focused on chemical disinfectants can play a crucial role. Fluid dynamics (Bhardwaj and Agrawal 2020 ), LEDs (Tseng and Li 2007 ; McDevitt et al 2012 ), surface treatment using carbon nanotubes (Kashyap and Saha 2020 ), nanocarbons like activated fullerene (Siddiquie et al 2020 ) and TiO 2 nanoparticles hydrophobic coating (Mahapatra et al 2020 ) along with many more strands of science need to focus and contribute to an area as common as sanitization.…”
Section: Discussionmentioning
confidence: 99%
“…Sanitization based research is a void where technologies and research other than those focused on chemical disinfectants can play a crucial role. Fluid dynamics (Bhardwaj and Agrawal 2020 ), LEDs (Tseng and Li 2007 ; McDevitt et al 2012 ), surface treatment using carbon nanotubes (Kashyap and Saha 2020 ), nanocarbons like activated fullerene (Siddiquie et al 2020 ) and TiO 2 nanoparticles hydrophobic coating (Mahapatra et al 2020 ) along with many more strands of science need to focus and contribute to an area as common as sanitization.…”
Section: Discussionmentioning
confidence: 99%
“…Another reported work showed that CNTs-coated PPE could eliminate the virus by employing a high-voltage charge based on the electrostatic principle. [94] This treatment destroys the virus when it comes in contact with the charged surface of a health worker. Furthermore, this fabricated PPE was reusable, thus making it economically friendlier.…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
“…Mahapatra et al ( 2020 ) proposed to combine anti-viral action with liquid-repelling properties to enhance the functionality of personal protective equipments (PPEs). Kashyap and Saha ( 2020 ) came up with novel idea of employing a high voltage charge generator from a very low DC source to eliminate the virus from the surface of PPE, with the aim of sanitizing it before and after use. Siddiquie et al ( 2020 ) proposed reduction in contact of viruses with surfaces by employing hydrophobic surfaces by texturing them.…”
Section: Development Of Computer Models and Apps For Managing The Panmentioning
confidence: 99%